Mechanical Properties of Glass Bead-Modified Polymer Composite. Issue 1 (January 2018) - Hsieh, Tsung-Han; Shen, Ming-Yuan; Huang, Yau-Shian; He, Qi-Qian; Chen, Hsuan-Chih
This present work investigated the adhesive effect of the material properties and fracture toughness of a thermosetting epoxy polymer modified with micron-sized glass beads. Various surface treatments were used to modify the surfaces of the glass beads in order to consider the effect of the glass bead particle/epoxy adhesion on the material properties and toughness of the polymer-based composites. Adding glass beads into polymer resulted in an increase in the modulus. The maximum value of the modulus was obtained for the polymer composite modified with well-bonded glass beads. The addition of the glass beads to polymers leads to a significant improvement in the fracture toughness. The particle/matrix adhesion strongly affects the toughness of the glass bead-modified polymers. The coupling agent silane treatment and release agent Frekote treatment caused well-bonded particles and poorly-bonded particles with the epoxy matrix. Both of the surface treatments result in a significant increase in the toughening performance. Toughening mechanisms of plastic void growth and crack deflection caused by the addition of the glass beads were found on the fracture surfaces of the tested specimens.